The joint action of unfolded protein response, circZc3h4, and circRNA Scar in procymidone‐induced testicular injury in adolescent mice. Issue 11 (1st August 2022) - Xin, Bingyan; Yu, Haiming; Li, Rui; Wang, Qing; Fu, Hu; Yan, Zhengli; Zhu, Yongfei
Abstract: Procymidone (PCM) is a low toxicity fungicide, and an endocrine‐disrupting chemical (EDC) that particularly damages the reproductive system of male vertebrates. In present study, adolescent mice in control, low‐, medium‐, and high‐dose groups were orally administered 0 (equal volume of soybean oil), 50, 100, and 200 mg/kg/day PCM, respectively, for 21 days. Additionally, a three‐dimensional culture of mouse testes was performed in vitro, and the control, low dose (0.33 × 10 −5  M), medium dose (1 × 10 −5  M), and high dose (3 × 10 −5  M) PCM groups were established. We have found that, under both in vivo and in vitro conditions, all doses of PCM caused damage to mouse testes. Moreover, the levels of circZc3h4 RNA and Zc3h4 decreased while miR‐212 increased in all treatment groups, with a corresponding rise in circRNA Scar and fall in Atp5b, compared to those in the control group, and all the changes showed a dose–response relationship. Besides, we have identified that low doses of PCM could activate the Ire1‐Xbp1 pathway, whereas the medium and high doses activated the Perk‐Elf2α‐Atf4, Ire1‐Xbp1, and Atf6 pathways. And it is, therefore, speculated that the unfolded protein response (UPR), circZc3h4 and circRNA Scar may have taken joint action in testicular injury in adolescent mice induced by PCM at the no observed adverse effect level (NOAEL, 100 mg/kg/day) and below NOAEL doses.